Analysis of North Jakarta 500 kV Extra High Voltage Transmission Line using Shunt Reactor - Djauhari, Fuad; Ruliyanta, Ruliyanta; Putra, Raden Tegar Satria; Keraf, Adhyartha (Jurnal Ilmiah Giga, 2024)
To meet the need for electrical energy in Indonesia, especially in DKI Jakarta, PT PLN (Persero) built the Muara Karang Combined-Cycle Power Plant (CCPP), which has daily start-stop facilities with a capacity of 500 MW and 500 kV extra high voltage overhead lines between Muara Karang – Duri Kosambi is 30 km long. In high voltage and extra high voltage transmission lines, channel filling appears where the receiving side voltage is greater or smaller than the sending side voltage. This research aims to design a shunt reactor for reactive power compensation that can overcome the problem of voltage differences. The modeling uses ETAP 20.0 software. The required shunt reactor value is 164.8 MVAR. There was a decrease in the reactive power produced at the Muara Karang CCPP plant by 157,878 MVAR due to installing a shunt reactor. So that it can improve the voltage drop on the load buses from Extra High Voltage Substation (EHVS) Duri Kosambi, with each having a voltage pu value on the Cengkareng GI bus of 92.52%, Duri Kosambi VVIP GI bus of 93.91%, Grogol Baru GI bus of 93.7%, and GIS Cengkareng at 94.25%. This can maintain reliability on the 500 kV Extra High Voltage Substation Muara Karang transmission line.